Humic Acid Coated Fe3O4 Nanoparticle for Phenol Sorption - Soerja Koesnarpadi; Sri Juari Santosa; Dwi Siswanta; Bambang Rusdiarso (Indonesian Journal of Chemistry, 2017)
The coating Fe3O4 using humic acid (HA) to form HA-coated Fe3O4 (Fe3O4/HA) was conducted and applied for phenol sorption. Fe3O4/HA was prepared using co-precipitation method in an alkaline condition using ammonium hydroxide and the addition of HA with mass ratios of Fe3O4 and HA=20:1, 10:1, 10:2, 10:3. The HA from peat soil in Sambutan village, East Kalimantan, Indonesia and was extracted in NaOH 0.1 M solution. The FT-IR characterization indicated that the coating of HA on the surface of Fe3O4 was successfully synthesized by forming a bond between the carboxylate group of HA and iron of Fe3O4. The coating of HA on the surface of Fe3O4 did not change the crystal structure of Fe3O4, but had lower peak intensities than Fe3O4 if added with HA with mass ratios 20:1, 10:1, 10:2, 10:3. The saturation magnetization of Fe3O4 decreased with the increased content of HA. SEM image indicated the magnetic particle size was almost homogenous by 10-18 nm. Iron and HA in Fe3O4/HA materials synthesized using different mass ratios were stable in pH range of 3.0-11.0 and 1.0–11.0, respectively. The phenol sorption on Fe3O4 was optimum at pH 5.0 and on Fe3O4/HA with mass ratios of 20:1, 10:1, 10:2, 10:3 were optimum at pH 5.0-6.0. The kinetics model for phenol adsorption on Fe3O4 and Fe3O4/HA with mass ratios of 20:1, 10:1, 10:2, 10:3 could be described using pseudo second-order equation and was in accordance with the Langmuir isotherm model with maximum adsorption capacity of 0.45 mmol/g for Fe3O4 and 0.55, 0.56, 0.58, 0.56 mmol/g respectively for Fe3O4/HA with mass ratios of 20:1, 10:1, 10:2, 10:3. The adsorption capacity increased with the increased content of HA, but the adsorption energy decreased except Fe3O4/HA with a mass ratio of 10:3. Generally, the performance of Fe3O4/HA materials was much higher than of bare Fe3O4.